Effects of Litsea cubeba essential oil on growth performance, blood antioxidation, immune function, apparent digestibility of nutrients, and fecal microflora of pigs - Chen, Fengming; Wang, Yushi; Wang, Kaijun; Chen, Jiayi; Jin, Ke; Peng, Kaiqiang; Chen, Xu; Liu, Zhimou; Ouyang, Jiang; Wang, Yong; Zhang, Xiaoya; Zou, Haowei; et al. (Frontiers in Pharmacology, 2023)
The purpose of this experiment was to investigate the effects of Litsea cubeba essential oil (LCO) on growth performance, blood antioxidation, immune function, apparent digestibility of nutrients and fecal microflora in fattening pigs. A total of 120 pigs were randomly assigned to five groups 6 replicate pens per treatment, 4 pigs per pen and fed basal diet, chlortetracycline, low, medium and high concentration LCO. The results of the study showed that dietary supplementation with different levels of LCO had a tendency to reduce the feed-to-weight ratio of pigs (P = 0.078). In addition, compared with the control treatment and CTC addition treatment of the basic diet, the catalase level in the serum of the pigs treated with 500 mg / kg LCO in the diet of finishing pigs was significantly increased (P < 0.05), the T-AOC and the levels of SOD, GSH-Px, GSH and MDA in serum of pigs were not significantly affected (P > 0.05). The apparent digestibility of CP, Ash and Ca in pigs with different levels of LCO were significantly increased compared with the control treatments fed the basal diet (P < 0.05). In addition, compared with the control treatment fed the basal diet and the treatment with CTC, the apparent digestibility of EE in pigs treated with medium-dose LCO was significantly increased (P < 0.05), and the apparent digestibility of pigs was significantly increased after the addition of low-dose LCO (P < 0.05). Among the genera, the percentage abundance of SMB53 (P < 0.05) was decreased in the feces of the CTC group when compared to that in the medium LCO group. At the same time, the relative abundance of L7A_E11 was markedly decreased in the feces of the Con, medium and high concentration LCO group than that in the CTC group (P < 0.05). In conclusion, adding a certain level of LCO in the diet of pig could improve the growth performance and blood physiological and biochemical conditions of pigs, and improve the antioxidant level of body and the efficiency of digestion and absorption of nutrients, and show the potential to replace antibiotics (CTC).